Long-term trends in cosmic rays and geomagnetic field secular variations - Elias, Ana Georgina (2021)
Cosmic rays are modulated by solar and geomagnetic activity. In addition, the flux that arrives to theEarth is sensitive to the inner geomagnetic field through its effect on the geomagnetic cutoff rigidity, Rc. This field has been decaying globally at a rate of ~5% per century from at least 1840. However, due to its configuration and non-uniform trend around the globe, its secular variation during the last decades has induced negative and positive Rc trends depending on location. In the present work, the database from the World Data Center for Cosmic Rays (WDCCR) is used to analyze long-term trend variations linked to geomagnetic secular variations. This database includes more than 100 stations covering, some of them, almost seven decades since the 1950?s. Those stations spanning more than 20 years of data are selected for the present study in order to adequately filter solar activity effects.